Heart rate and EEG gamma band connectivity in the ventral attention network during emotional movie stimulation in women with high emotion dysregulation - Fusina, Francesca; Marino, Marco; Angrilli, Alessandro (Frontiers in Neuroscience, 2025)
IntroductionThe heart-brain connection represents an interesting innovative framework for investigating the complex and reciprocal influences between the cardiovascular system and brain activity in emotion research. The present study aimed at investigating the correlation between heart rate and connectivity within brain regions relevant for interoception and emotional regulation (i.e., the Ventral Attention Network) during ecological stimulation with validated emotional video-clips.MethodsTo this end two groups of 25 healthy female students were enrolled (mean age 22.62 ± 1.87SD), after a selection from 422 students, based on questionnaires measuring emotion dysregulation. Both the High Dysregulation (HD) and Low Dysregulation (LD) groups watched 18 validated video-clips divided in 6 different emotional categories (Erotic, Scenery, Neutral, Sadness, Compassion and Fear) while EEG from 64 electrodes and heart rate (HR) were recorded. Focusing on alpha and gamma EEG rhythms, the connectivity within the VAN network and between VAN and other five relevant networks (DAN, DMN, LN, SMN, VN) was computed and then correlated with the heart rate.ResultsResults showed a different pattern of HR-Network-connectivity correlation in the two groups. EEG Gamma band evidenced several effects only in the HD group with significant positive HR-Network-connectivity correlations for most networks during the Sadness and Neutral movies and to a less extent for Scenery clips (all rs ≥ 0.29, p < 0.05).DiscussionThe consistent correlation in HD during Sadness clips points to the relevance of this emotion as a synchronizing agent coordinating cardiovascular and central cortical responses. Unlike the HD, the LD group showed, in the alpha EEG band only, a negative HR-Brain-connectivity correlation in three networks during the Erotic clips, a result that highlights a normal increased attention (bradycardic response) towards relevant biological appetitive cues, while the HD group had an opposite pattern with positive HR- Brain correlation to Erotic in the gamma band that could be explained by greater sexual issues and embarrassment to these stimuli in HD individuals.